2016
DOI: 10.2215/cjn.08070715
|View full text |Cite
|
Sign up to set email alerts
|

Long–Term Renal Outcomes after Cisplatin Treatment

Abstract: Background and objectives Nephrotoxicity remains the dose-limiting side effect of cisplatin, an effective chemotherapeutic agent with applications across diverse tumor types. This study presents data on renal outcomes across multiple tumor types in 821 adults. We report on incidence of AKI, initial and long-term changes in eGFR after cisplatin, and relationships between cumulative dose, initial eGFR, age, sex, and long-term renal function.Design, setting, participants, & measurements This was a retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
137
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(148 citation statements)
references
References 22 publications
(30 reference statements)
5
137
1
5
Order By: Relevance
“…Oxidative stress is involved in the pathogenesis of CDDP-induced dose-limiting toxicities, including nephrotoxicity [30], ototoxicity [31], and peripheral neuropathy [32]. We examined oxidative stress production in hippocampal neurons and NSCs following CDDP treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress is involved in the pathogenesis of CDDP-induced dose-limiting toxicities, including nephrotoxicity [30], ototoxicity [31], and peripheral neuropathy [32]. We examined oxidative stress production in hippocampal neurons and NSCs following CDDP treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, investigation into these cases suggests other reasons for ATN on kidney biopsy. As an example, two of five patients underwent prior platinum therapy which is nephrotoxic and known to cause ATN (20,21). Further, the majority of these patients had more cardiovascular risk factors and marked histologic vascular lesions on kidney biopsy (13).…”
mentioning
confidence: 99%
“…AKI can result from a variety of insults including volume depletion, septicemia, hypotension, and commonly used drugs including antibiotics and chemotherapeutic agents.Cisplatin is a widely used chemotherapy in the treatment of a variety of cancers including ovarian, head and neck, bladder, testicular, and lung, among others 6,7 . A significant side effect of cisplatin therapy is the occurrence of AKI in approximately 33% of patients 8,9 . Indeed, it has been reported that about 20% of all AKI incidences are caused by cisplatin 7,10 .…”
mentioning
confidence: 99%
“…Indeed, it has been reported that about 20% of all AKI incidences are caused by cisplatin 7,10 . The development of AKI in these patients can result in the interruption of chemotherapy or a change to less effective chemotherapies 8,9 . There is therefore a critical need to develop novel strategies to prevent or treat AKI induced by cisplatin.…”
mentioning
confidence: 99%